6.152 Problems 15101 to 15200

Table 6.303: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

15101

\[ {}x y^{\prime }+\left (5 x +2\right ) y = \frac {20}{x} \]

15102

\[ {}2 \sqrt {x}\, y^{\prime }+y = 2 x \,{\mathrm e}^{-\sqrt {x}} \]

15103

\[ {}y^{\prime }-3 y = 6 \]

15104

\[ {}y^{\prime }-3 y = 6 \]

15105

\[ {}y^{\prime }+5 y = {\mathrm e}^{-3 x} \]

15106

\[ {}x y^{\prime }+3 y = 20 x^{2} \]

15107

\[ {}x y^{\prime } = y+x^{2} \cos \left (x \right ) \]

15108

\[ {}\left (x^{2}+1\right ) y^{\prime } = x \left (3+3 x^{2}-y\right ) \]

15109

\[ {}y^{\prime }+6 x y = \sin \left (x \right ) \]

15110

\[ {}x^{2} y^{\prime }+x y = \sqrt {x}\, \sin \left (x \right ) \]

15111

\[ {}x y^{\prime }-y = x^{2} {\mathrm e}^{-x^{2}} \]

15112

\[ {}y^{\prime } = \frac {1}{\left (3 x +3 y+2\right )^{2}} \]

15113

\[ {}y^{\prime } = \frac {\left (3 x -2 y\right )^{2}+1}{3 x -2 y}+\frac {3}{2} \]

15114

\[ {}\cos \left (-4 y+8 x -3\right ) y^{\prime } = 2+2 \cos \left (-4 y+8 x -3\right ) \]

15115

\[ {}y^{\prime } = 1+\left (y-x \right )^{2} \]

15116

\[ {}x^{2} y^{\prime }-x y = y^{2} \]

15117

\[ {}y^{\prime } = \frac {y}{x}+\frac {x}{y} \]

15118

\[ {}\cos \left (\frac {y}{x}\right ) \left (y^{\prime }-\frac {y}{x}\right ) = 1+\sin \left (\frac {y}{x}\right ) \]

15119

\[ {}y^{\prime } = \frac {x -y}{x +y} \]

15120

\[ {}y^{\prime }+3 y = 3 y^{3} \]

15121

\[ {}y^{\prime }-\frac {3 y}{x} = \frac {y^{2}}{x^{2}} \]

15122

\[ {}y^{\prime }+3 y \cot \left (x \right ) = 6 \cos \left (x \right ) y^{{2}/{3}} \]

15123

\[ {}y^{\prime }-\frac {y}{x} = \frac {1}{y} \]

15124

\[ {}y^{\prime } = \frac {y}{x}+\frac {x^{2}}{y^{2}} \]

15125

\[ {}3 y^{\prime } = -2+\sqrt {2 x +3 y+4} \]

15126

\[ {}3 y^{\prime }+\frac {2 y}{x} = 4 \sqrt {y} \]

15127

\[ {}y^{\prime } = 4+\frac {1}{\sin \left (4 x -y\right )} \]

15128

\[ {}\left (y-x \right ) y^{\prime } = 1 \]

15129

\[ {}\left (x +y\right ) y^{\prime } = y \]

15130

\[ {}\left (2 x y+2 x^{2}\right ) y^{\prime } = x^{2}+2 x y+2 y^{2} \]

15131

\[ {}y^{\prime }+\frac {y}{x} = x^{2} y^{3} \]

15132

\[ {}y^{\prime } = 2 \sqrt {2 x +y-3}-2 \]

15133

\[ {}y^{\prime } = 2 \sqrt {2 x +y-3} \]

15134

\[ {}x y^{\prime }-y = \sqrt {x y+x^{2}} \]

15135

\[ {}y^{\prime }+3 y = \frac {28 \,{\mathrm e}^{2 x}}{y^{3}} \]

15136

\[ {}y^{\prime } = \left (x -y+3\right )^{2} \]

15137

\[ {}y^{\prime }+2 x = 2 \sqrt {x^{2}+y} \]

15138

\[ {}\cos \left (y\right ) y^{\prime } = {\mathrm e}^{-x}-\sin \left (y\right ) \]

15139

\[ {}y^{\prime } = x \left (1+\frac {2 y}{x^{2}}+\frac {y^{2}}{x^{4}}\right ) \]

15140

\[ {}y^{\prime } = \frac {1}{y}-\frac {y}{2 x} \]

15141

\[ {}{\mathrm e}^{x y^{2}-x^{2}} \left (y^{2}-2 x \right )+2 \,{\mathrm e}^{x y^{2}-x^{2}} x y y^{\prime } = 0 \]

15142

\[ {}2 x y+y^{2}+\left (2 x y+x^{2}\right ) y^{\prime } = 0 \]

15143

\[ {}2 x y^{3}+4 x^{3}+3 y^{2} y^{\prime } x^{2} = 0 \]

15144

\[ {}2-2 x +3 y^{\prime } y^{2} = 0 \]

15145

\[ {}1+3 x^{2} y^{2}+\left (2 x^{3} y+6 y\right ) y^{\prime } = 0 \]

15146

\[ {}4 x^{3} y+\left (x^{4}-y^{4}\right ) y^{\prime } = 0 \]

15147

\[ {}1+\ln \left (x y\right )+\frac {x y^{\prime }}{y} = 0 \]

15148

\[ {}1+{\mathrm e}^{y}+x \,{\mathrm e}^{y} y^{\prime } = 0 \]

15149

\[ {}{\mathrm e}^{y}+\left (x \,{\mathrm e}^{y}+1\right ) y^{\prime } = 0 \]

15150

\[ {}1+y^{4}+x y^{3} y^{\prime } = 0 \]

15151

\[ {}y+\left (y^{4}-3 x \right ) y^{\prime } = 0 \]

15152

\[ {}\frac {2 y}{x}+\left (4 x^{2} y-3\right ) y^{\prime } = 0 \]

15153

\[ {}1+\left (1-x \tan \left (y\right )\right ) y^{\prime } = 0 \]

15154

\[ {}3 y+3 y^{2}+\left (2 x +4 x y\right ) y^{\prime } = 0 \]

15155

\[ {}2 x \left (1+y\right )-y^{\prime } = 0 \]

15156

\[ {}2 y^{3}+\left (4 x^{3} y^{3}-3 x y^{2}\right ) y^{\prime } = 0 \]

15157

\[ {}4 x y+\left (3 x^{2}+5 y\right ) y^{\prime } = 0 \]

15158

\[ {}6+12 x^{2} y^{2}+\left (7 x^{3} y+\frac {x}{y}\right ) y^{\prime } = 0 \]

15159

\[ {}x y^{\prime } = 2 y-6 x^{3} \]

15160

\[ {}x y^{\prime } = 2 y^{2}-6 y \]

15161

\[ {}4 y^{2}-x^{2} y^{2}+y^{\prime } = 0 \]

15162

\[ {}y^{\prime } = \sqrt {x +y} \]

15163

\[ {}x^{2} y^{\prime }-\sqrt {x} = 3 \]

15164

\[ {}x y y^{\prime }-y^{2} = \sqrt {x^{2} y^{2}+x^{4}} \]

15165

\[ {}y^{\prime } = y^{2}-2 x y+x^{2} \]

15166

\[ {}4 x y-6+x^{2} y^{\prime } = 0 \]

15167

\[ {}x y^{2}-6+x^{2} y y^{\prime } = 0 \]

15168

\[ {}x^{3}+y^{3}+y^{2} y^{\prime } x = 0 \]

15169

\[ {}3 y-x^{3}+x y^{\prime } = 0 \]

15170

\[ {}1+2 x y^{2}+\left (2 x^{2} y+2 y\right ) y^{\prime } = 0 \]

15171

\[ {}3 x y^{3}-y+x y^{\prime } = 0 \]

15172

\[ {}2+2 x^{2}-2 x y+\left (x^{2}+1\right ) y^{\prime } = 0 \]

15173

\[ {}\left (y^{2}-4\right ) y^{\prime } = y \]

15174

\[ {}\left (x^{2}-4\right ) y^{\prime } = x \]

15175

\[ {}y^{\prime } = \frac {1}{x y-3 x} \]

15176

\[ {}y^{\prime } = \frac {3 y}{1+x}-y^{2} \]

15177

\[ {}\sin \left (y\right )+\left (x +y\right ) \cos \left (y\right ) y^{\prime } = 0 \]

15178

\[ {}\sin \left (y\right )+\left (1+x \right ) \cos \left (y\right ) y^{\prime } = 0 \]

15179

\[ {}\sin \left (x \right )+2 \cos \left (x \right ) y^{\prime } = 0 \]

15180

\[ {}x y y^{\prime } = 2 x^{2}+2 y^{2} \]

15181

\[ {}y^{\prime } = \frac {x +2 y}{x +2 y+3} \]

15182

\[ {}y^{\prime } = \frac {x +2 y}{2 x -y} \]

15183

\[ {}y^{\prime } = \frac {y}{x}+\tan \left (\frac {y}{x}\right ) \]

15184

\[ {}y^{\prime } = x y^{2}+3 y^{2}+x +3 \]

15185

\[ {}1-\left (x +2 y\right ) y^{\prime } = 0 \]

15186

\[ {}\ln \left (y\right )+\left (\frac {x}{y}+3\right ) y^{\prime } = 0 \]

15187

\[ {}y^{2}+1-y^{\prime } = 0 \]

15188

\[ {}y^{\prime }-3 y = 12 \,{\mathrm e}^{2 x} \]

15189

\[ {}x y y^{\prime } = y^{2}+x y+x^{2} \]

15190

\[ {}\left (x +2\right ) y^{\prime }-x^{3} = 0 \]

15191

\[ {}x y^{3} y^{\prime } = y^{4}-x^{2} \]

15192

\[ {}y^{\prime } = 4 y-\frac {16 \,{\mathrm e}^{4 x}}{y^{2}} \]

15193

\[ {}2 y-6 x +\left (1+x \right ) y^{\prime } = 0 \]

15194

\[ {}x y^{2}+\left (x^{2} y+10 y^{4}\right ) y^{\prime } = 0 \]

15195

\[ {}y y^{\prime }-x y^{2} = 6 x \,{\mathrm e}^{4 x^{2}} \]

15196

\[ {}\left (y-x +3\right )^{2} \left (y^{\prime }-1\right ) = 1 \]

15197

\[ {}x +y \,{\mathrm e}^{x y}+x \,{\mathrm e}^{x y} y^{\prime } = 0 \]

15198

\[ {}y^{2}-y^{2} \cos \left (x \right )+y^{\prime } = 0 \]

15199

\[ {}y^{\prime }+2 y = \sin \left (x \right ) \]

15200

\[ {}y^{\prime }+2 x = \sin \left (x \right ) \]